Individual patient data meta-analysis of combined treatments versus psychotherapy (with or without pill placebo), pharmacotherapy or pill placebo for adult depression: a protocol. Issue 2 (13th February 2017) - Weitz, Erica; Kleiboer, Annet; van Straten, Annemieke; Hollon, Steven D; Cuijpers, Pim
Abstract : Introduction: There are many proven treatments (psychotherapy, pharmacotherapy or their combination) for the treatment of depression. Although there is growing evidence for the effectiveness of combination treatment (psychotherapy + pharmacotherapy) over pharmacotherapy alone, psychotherapy alone or psychotherapy plus pill placebo, for depression, little is known about which specific groups of patients may respond best to combined treatment versus monotherapy. Conventional meta-analyses techniques have limitations when tasked with examining whether specific individual characteristics moderate the effect of treatment on depression. Therefore, this protocol outlines an individual patient data (IPD) meta-analysis to explore which patients, with which clinical characteristics, have better outcomes in combined treatment compared with psychotherapy (alone or with pill placebo), pharmacotherapy and pill placebo. Methods and Analysis: Study searches are completed using an established database of randomised controlled trials (RCTs) on the psychological treatment of adult depression that has previously been reported. Searches were conducted in PubMed, PsycInfo, Embase and the Cochrane Central Register of Controlled Trials. RCTs comparing combination treatment (psychotherapy + pharmacotherapy) with psychotherapy (with or without pill placebo), pharmacotherapy or pill placebo for the treatment of adult depression will be included. Study authors of eligible trials will be contacted and asked to contribute IPD. Conventional meta-analysis techniques will be used to examine differences between studies that have contributed data and those that did not. Then, IPD will be harmonised and analysis using multilevel regression will be conducted to examine effect moderators of treatment outcomes. Dissemination: Study results outlined above will be published in peer-reviewed journals. Study results will contribute to better understanding whether certain patients respond best to combined treatment or other depression treatments and provide new information on moderators of treatment outcome that can be used by patients, clinicians and researchers. Trial registration number: CRD42016039028.